"Z levicového intelektuála proamerickým liberálem?" Vývoj myšlení prezidenta Václava Havla ve vztahu k USA a NATO - Libnar, Vojtěch (Univerzita Karlova, Filozofická fakulta, 2023)
The diploma thesis deals with selected views of Václav Havel after 1989, taking into account his previous ideas. It traces the development of Václav Havel's attitudes towards the North Atlantic Alliance, the contemplated, prepared and finally realized membership of the Czech Republic in this organization. Furthermore, the thesis examines Havel's personal ties to selected American officials and reflects on their views of Václav Havel. These include Presidents George H. W. Bush, Bill Clinton, George W. Bush, and Secretary of State Madeleine Albright. The thesis then turns in the final section to Havel's views on selected military interventions that were directly led by, or in which the United States was the major force - the Gulf War, the bombing of Yugoslavia, and the invasion of Iraq. Through these perspectives, it seeks to answer the question of whether Havel's worldview changed fundamentally during his presidency, and whether Havel uncritically embraced support for American foreign policy. Whether Havel had turned from a rather left-leaning intellectual from dissident circles into a Central European post-Communist statesman who was absorbed by the triumphalist atmosphere of the 1990s and his admiration for the United States. Or whether Havel has partly maintained his critical distance and lived. Diplomová práce se zabývá vybranými názory Václava Havla po roce 1989 s přihlédnutím k jeho předchozím myšlenkovým východiskům. Sleduje vývoj postojů Václava Havla k Severoatlantické alianci, uvažovanému, připravovanému a nakonec uskutečněnému členství České republiky v této organizaci. Dále práce zkoumá Havlovy osobní vazby na vybrané americké představitele a reflektuje také jejich pohled na Václava Havla. Jde o prezidenty George H. W. Bushe, Billa Clintona, George W. Bushe a ministryni zahraničí Madeleine Albrightovou. Práce se poté v závěrečné části věnuje Havlovým názorům na vybrané vojenské intervence, které přímo vedly nebo v nichž byly hlavní silou Spojené státy americké - válce v Perském zálivu, bombardování ...